Hubungan Family Centered Care dan Kepatuhan Terapi dengan Kualitas Hidup pada Pasien TB Paru - Ferlia, Reni; Palupi, Rini; Kusuma, Anggi; Kameliawati, Feri (Wiraraja Medika : Jurnal Kesehatan, 2025)
Tuberculosis (pulmonary TB) is an infectious disease caused by Mycobacterium tuberculosis, and is one of the 10 leading causes of death in the world. Patients with pulmonary tuberculosis often experience low quality of life, which can negatively impact their adherence to therapy, potentially resulting in treatment failure or even death. Since 2016, individuals with pulmonary tuberculosis have experienced a declining treatment success rate. One strategy to increase access to healthcare is through Family Centered Care, which emphasizes the value of family participation in patient care initiatives. The research objective was to determine the correlation between family centered care and therapy compliance with the life quality of pulmonary TB patients at Jend Ahmad Yani Hospital of Metro. The research type was quantitative with descriptive correlational research design using cross-sectional. The population in the study was 80 people who were still undergoing treatment. The sampling size was determined by total sampling. The instruments used in this research were the family care questionnaire, MMAS-8, and Short From-36 (SF-36). Data analysis used the Gamma statistical test and the Chi-Square test. The statistical test results show that there is a correlation between family-centered care and the quality of life of pulmonary TB patients at Jend Ahmad Yani Hospital of Metro with a p-value of 0.002 and the statistical test results show that there is a correlation between therapy compliance and the life quality pulmonary TB patients at Jend Ahmad Yani Hospital of Metro. This is intended to raise awareness of the significance of treatment adherence and family participation in enhancing the quality of life for patients with pulmonary tuberculosis. Information from communication initiatives utilizing booklets, films, pamphlets, and other media can be obtained through additional study.